FIRST REPORT OF THE GENUS AETHIOPELLA HANDSCHIN, 1942 AND SPECIES FOLSOMIA INOCULATA STACH, 1947 (HEXAPODA, COLLEMBOLA) FROM IRAN (Acta Entomologica Serbica, 2020)
Collembola are a widespread and abundant group of arthropods with distribution all over the world. Collembola fauna is less well-known in the northern districts of Iran. This study was conducted to investigate the Collembola fauna in the forests of Mazandaran province, North Iran, during 2016. During this study, 13 genera and 9 species belonging to 6 families were found. The genus Aethiopella Handschin, 1942 and the species Folsomia inoculata Stach, 1947 are reported for the first time from Iran, with the genus Arrhopalites Börner, 1906 recorded for the first time from Mazandaran province.